(untitled) (International Journal of Environmental Sciences, 2025)
Illicit or unreported alcohol—commonly referred to as country-made or spurious liquor—poses a significant public health risk globally, with a particularly severe impact in developing countries like India. As the third-largest producer of alcoholic beverages in the world, India faces a growing challenge in controlling the adulteration of alcohol, especially with toxic substances such as methanol. Chhattisgarh, in particular, reports a higher prevalence of alcohol consumption compared to many other Indian states. The present study was conducted to detect adulterants in illicit liquor samples collected from various districts across Chhattisgarh, including Bilaspur, Jangir-Champa, Jashpur, Bastar, Korba, Sarangarh, Ambikapur, Sakti, Mahasamund, and Raigarh.Preliminary analysis of the samples was carried out using a series of qualitative colour tests to identify key constituents. The results indicated the presence of ethanol in all samples. No traces of other toxic adulterants such as furfural, urea, iron, or copper were detected. However, methanol—a highly toxic alcohol—was identified in one sample collected from Bilaspur.Further quantitative analysis was performed using a relative density bottle to determine alcohol content and sample density. Advanced techniques such as Fourier-transform infrared spectroscopy (FTIR) were employed to characterize functional groups and confirm the presence of various chemical components. This study underscores the importance of routine forensic surveillance of illicit alcohol to prevent methanol poisoning and ensure public safety.